2000
DOI: 10.2134/jeq2000.00472425002900010031x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spp. and Fecal Coliform Loads in Coastal Waters from a Point vs. Nonpoint Source of Pollution

Abstract: Coastal areas are often contaminated by the dissemination of pathogenic bacteria from terrestrial inputs. In this study, we compared fecal conforms (FC) and Salmonella spp.loads from a coastal Mediterranean river and from the submarine outfall of a coastal wastewater treatment station. A stratified sampling strategy was used to analyze storm events. Bacterial Boxes were estimated during a 16-mo period. Salmonella spp. loads from the river were high during storm events, and the annual loads were higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 15 publications
7
49
0
Order By: Relevance
“…Their presence in water, therefore, indicates faecal contamination. Sewage effluents, agricultural run-off and direct deposit of faecal materials from wild animals and birds are the major sources of the bacteria in aquatic environments (Alcaide et al, 1984;Baudart et al, 2000;Johnson et al, 2003;Abulreesh et al, 2005). Salmonella species have been found in almost all types of aquatic environments that receive faecal contamination, that include drinking water (Bhatta et al, 2007), rivers (Pianetti et al, 1998;Polo et al, 1998;Polo et al, 1999;Dionisio et al, 2000;Lemarchand & Lebaron, 2003;Arvanitidou et al, 2005;Haley et al, 2009), lakes (Claudon et al, 1971;Arvanitidou et al, 1995;Sharma & Rajput, 1996), ponds (Shellenbarger et al, 2008), marine waters (Matinez-Urtaza et al, 2004a;Martinez-Urtaza et al, 2004b;Martinez-Urtaza & Liebana, 2005;Harakeh et al, 2006), run-off water (Claudon et al, 1971), treated and untreated wastewater (Ho & Tam, 2000;Melloul et al, 2002;Espigares et al, 2006, Mafu et al, 2009 worldwide.…”
Section: Aquatic Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their presence in water, therefore, indicates faecal contamination. Sewage effluents, agricultural run-off and direct deposit of faecal materials from wild animals and birds are the major sources of the bacteria in aquatic environments (Alcaide et al, 1984;Baudart et al, 2000;Johnson et al, 2003;Abulreesh et al, 2005). Salmonella species have been found in almost all types of aquatic environments that receive faecal contamination, that include drinking water (Bhatta et al, 2007), rivers (Pianetti et al, 1998;Polo et al, 1998;Polo et al, 1999;Dionisio et al, 2000;Lemarchand & Lebaron, 2003;Arvanitidou et al, 2005;Haley et al, 2009), lakes (Claudon et al, 1971;Arvanitidou et al, 1995;Sharma & Rajput, 1996), ponds (Shellenbarger et al, 2008), marine waters (Matinez-Urtaza et al, 2004a;Martinez-Urtaza et al, 2004b;Martinez-Urtaza & Liebana, 2005;Harakeh et al, 2006), run-off water (Claudon et al, 1971), treated and untreated wastewater (Ho & Tam, 2000;Melloul et al, 2002;Espigares et al, 2006, Mafu et al, 2009 worldwide.…”
Section: Aquatic Environmentsmentioning
confidence: 99%
“…Furthermore, Salmonella spp. were successfully detected in Spanish fresh and marine water that received faecal pollution in the absence of faecal indicators, as well as in aquatic environments with low degree of pollution (Pianetti et al, 1998;Baudart et al, 2000;Dionisio et al, 2000). Thus, the ability of faecal indicators to predict the presence of salmonellae in polluted environmental waters remains questionable, and the absence of faecal indicators is not always a reliable indication of the absence of Salmonella spp.…”
Section: Aquatic Environmentsmentioning
confidence: 99%
“…Fecal pollution is a serious environmental problem that affects many coastal and inland waters worldwide (1,3,4,14). Point source discharges such as raw sewage, storm water, combined sewer overflows, effluents from wastewater treatment plants, and industrial sources are considered the major contributors to fecal pollution (22).…”
mentioning
confidence: 99%
“…The quality and Baudart et al (2000) showed that Salmonella trapped in sediment particles accumulated in the riverbed during low water levels downstream of a river course and were re-suspended during storm events. In another study, the loads of Salmonella spp.…”
Section: Total Bacterial Dna Extractionmentioning
confidence: 99%